RELATIONSHIP OF SODIUM INTAKE AND BODY MASS INDEX WITH BLOOD PRESSURE IN CHRONIC KIDNEY DISEASE PATIENTS WHEN UNDERGOING HEMODIALYSIS IN RSUD IBNU SINA KABUPATEN GRESIK - Mas'udatus Saniyah; Dian Agnesia; Ernawati Ernawati (Universitas Muhammadiyah Gresik, 2021)
This study aims to analyze the relationship between sodium intake and Body Mass Index (BMI) with blood pressure in Chronic Kidney Disease (CKD) patients undergoing hemodialysis (HD). This type of research uses observational analytic with cross sectional approach. The total subject was 72 CKD patients undergoing hemodialysis at the RSUD Ibnu Sina Kabupaten Gresik, which were taken using the total sampling technique. Data was collected using a questionnaire, Food Recall 2x24 hour and measurements of body weight, height, and blood pressure. Data analysis was performed using the Chi-Square test and Linear Regression test. The univariate results showed that 58.3% of patients had more sodium intake, 59.7% had normal BMI, and 69.4% of patients had hypertension. The bivariate results showed that there was a relationship between sodium intake and blood pressure (p=0.000) and there was no relationship between BMI and blood pressure (p=0.145). The multivariate results showed that there was a strong relationship between sodium intake and blood pressure (R=0.646). The conclusion of this study is that blood pressure in CKD patients undergoing HD is more related to sodium intake than with BMI. So it is necessary to have education about limiting sodium intake in order to get optimal nutritional health.